Upaya Pemulihan Trauma pada Anak Korban Kekerasan Seksual di Pusat Pelayanan Terpadu (PPT) Jayandu Widuri Kabupaten Pemalang - Ayu Faiza Algifahmy; Ratih Hanifah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The phenomenon of sexual violence against children is an act of bullying that targets children under the age of 18 and causes physical misery, psychological and social trauma. Seeing the risk of very dangerous trauma reactions requires recovery treatment carried out by professionals to reduce reactions and consequences that arise in the future. This research uses a descriptive qualitative research method with data sources consisting of families of victims of sexual violence, leaders and assistants, and psychologists. Data collection techniques use interviews, observation and documentation. Test the validity and reliability of the data using two triangulations, namely source triangulation and technique triangulation. Data analysis techniques use data reduction, data display, and data verification. The research results showed that children who were victims of sexual violence at PPT Jayandu Widuri, Pemalang Regency experienced trauma reactions such as blaming themselves, losing trust in adults, exploiting their sexual experiences, feeling helpless, stigma, eroticization, and destructive acts. Efforts to recover the trauma of children who are victims of sexual violence are through collaboration between mentoring, counseling and therapy. By doing this, children and families will be more motivated to participate in activities, become confident and stronger during the legal and trial stages, and can return to a better situation.